2004
DOI: 10.1111/j.1447-0578.2004.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected single blastocyst transfers maintained pregnancy outcome and eliminated multiple pregnancies

Abstract: Transfer of more than one embryo following fertilization/intracytoplasmic sperm injection cycles have increased pregnancy rate at the cost of increasing the incidence of triplets and twins. It has been proposed that prolonged culture to the blastocyst stage would automatically result in the selection of good quality embryos for transfer and minimize the incidence of triplets and twins. The objectives of the present retrospective analysis were to examine the pregnancy outcome, multiple pregnancy and related dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In this series, pregnancy rate, implantation rate, and multiple pregnancy rate were lower in patients over 35 years old than in those below 34, although the difference between two age groups was not significant. The result was similar to that reported by Kuramoto et al 9 . Multiple pregnancy was not seen in patients over 36 years old.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this series, pregnancy rate, implantation rate, and multiple pregnancy rate were lower in patients over 35 years old than in those below 34, although the difference between two age groups was not significant. The result was similar to that reported by Kuramoto et al 9 . Multiple pregnancy was not seen in patients over 36 years old.…”
Section: Discussionsupporting
confidence: 92%
“…Feasibility of elective single embryo transfer in cleavage‐stage embryos (eSET) initially was demonstrated retrospectively after judging the quality of embryos transferred in double embryo transfer (DET) procedures. The answer to the question of what grade of blastocyst represents a putative high competence (PHC) embryo is an unresolved question, although many studies have reported that blastocyst transfer offers a higher implantation rate than transfer of cleavage‐stage embryos 8–16 . Most blastocyst transfer programs are intended for selected groups of patients, so even randomized controlled studies involve self‐selection bias 8 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to early‐stage embryos, blastocysts represent more mature, naturally selected embryos with a higher potential for development and implantation after in vitro fertilization (IVF) . From the viewpoint of vitrified blastocyst transfer programs, assisted reproductive technology requires that blastocysts be completely vitrified to enhance the IVF success rate . However, Vanderzwalmen et al found that the survival rate after vitrification/warming depended on the stage of blastocyst development, with expanded blastocysts exhibiting lower survival rate than morulae or early cavitating blastocysts.…”
Section: Introductionmentioning
confidence: 99%
“…Oocytes were retrieved under transvaginal ultrasound guidance 34 to 35 hours after hCG injection and subjected to conventional IVF-ICSI procedures (day 0) (17). After insemination, oocytes were cultured individually in 20-mL droplets of BlastAssist System medium (Origio, Jyllinge, Denmark) or Sydney IVF sequential medium (Cook, Brisbane, Australia) at 37 C in a humidified atmosphere of 6% CO 2 , 5% O 2 , and 89% N 2 .…”
mentioning
confidence: 99%